Climate variability and water resources in West Africa: current situation and outlook - (:unkn) unknown (My University, 2006)
Within the framework of the International Decade for Action on Water 2005-2015 “Water for People, Water for Life”, water resource issues need to be made better known to a wider public, particularly in the context of West Africa.This public presentation was given at the Muséum d'Histoire Naturelle in Grenoble, at the request of the African Monsoon Multidisciplinary Approach (AMMA) project of the Laboratoire d'étude des Transferts en Hydrologie et Environnement (LTHE) in Grenoble.
Keywords: African Research